Medicine Delivery Robot Using Arduino Based on Android Control - Hayadi Hamuda; Anjar Setiawan (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2026)
Pharmacies are experiencing increasing pressure in delivering healthcare services due to rising demand driven by the spread of infectious diseases. This surge often results in service delays and increased physical interaction between medical staff and patients, reducing operational efficiency and elevating health risks. This study proposes the development of an intelligent medicine delivery robot to enhance pharmaceutical service quality and minimize direct contact. The system is built using an Arduino Uno R4 WiFi integrated with Bluetooth HC-05 communication, TCRT5000 line-following sensors, DC motor drivers, and a 2×16 LCD interface, with control implemented via the MIT App Inventor platform. Experimental evaluation demonstrates that the robot achieves a navigation accuracy of 92% on predefined tracks and successfully delivers medication within a maximum operational range of 27 meters. The system reduces direct human interaction by approximately 65% and improves service response time by 40% compared to conventional manual delivery methods. The proposed contribution lies in the integration of mobile-based control with autonomous delivery features in a low-cost embedded system, offering a practical and scalable solution for smart pharmacy services.